Pelikula a documentary on Philippine film : 1897-1960 - Sotto, Agustin (Tuklas sining series, 1992)
Explores the origins of local Philippine film and cinema from the late 19th century until the mid-20th century. Discusses key contributors and films, as well as their social and political influences on society.